The impact of osteoporosis on health-related quality of life in patients after liver transplantation – a pilot study - Raszeja-Wyszomirska, Joanna; Kucharski, Robert; Kotarska, Katarzyna; Zalewska, Marta; Miazgowski, Tomasz (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Introduction : Liver transplantation (LT) is now a well-established procedure with 5-year survival rates over 70%, and one of its ultimate goals is the improvement of patient health-related quality of life (HRQOL). Osteoporosis remains a serious potential complication of LT, leading to fragility fractures, pain, and functional impairment. Aim: To assess the degree of osteoporosis and the impact of fragility fractures on HRQOL in patients with chronic liver diseases treated with LT. Material and methods : Twenty-seven patients (14 female, 13 male) at a median period of 3.5 years post LT participated in the study. HRQOL was assessed by Short Form-36 and PBC-40 instruments. Bone mineral density (BMD) in the lumbar spine and hip neck were measured by dual-energy X-ray absorptiometry. Physical activity was assessed by questionnaire. Data on the duration of the liver disease, time from LT, and fragility fractures were also collected. Results : As many as 74.1% of the patients had reduced BMD (t-score < 1.0 SD) in the hip. Mean values of the spine and hip BMD z-scores were 1.1 and 0.9 SD, respectively. Time after LT, percentage of lean tissue, and physical activity were positively associated with BMD. The prevalence of fractures was 48%. We did not find significant differences in age, gender, body composition parameters, physical activity, BMD, and HRQOL scores between the subjects with and without fractures. Conclusions : We found a high prevalence of fragility fractures and a decreased BMD in LT recipients. Patients with a history of fractures had similar HRQOL scores to those without fractures.